Heart rate pro ile and heart rate variability in volleyball athletes: a systematic review with meta-analyses - Cardoso, Ananda Silveira (2022)
Background: Physiological parameters can be objectively measured for controlling and quantifying physical activity levels. Aims: This study aimed to systematically review the literature on volleyball athletes' profile regarding heart rate (HR) and HR variability (HRV). Methods: PubMed, Scopus, Embase and SportDiscus databases were searched to find studies presenting resting HR, maximal HR, mean HR and time domain HRV during training sessions and matches. Results: Volleyball athletes' profile was HRrest 66 ± 2.5 bpm (minimum 41 ± 10 bpm; maximum 82.4 ± 2.1 bpm), HRmax was 184 ± 1.3 bpm (minimum 170 ± 8.0 bpm; maximum 192 ± 3.0 bpm), HRtraining data was in average 150 ± 12 bpm (minimum 124.8 ± 6.2 bpm; maximum 171.5 ± 11.0 bpm) and mean HRmatch was 154 ± 5.5 bpm (minimum 105.3 ± 12.8 bpm; maximum 182.3 ± 5.2 bpm). The RR interval data resulting in a mean value of 1096 ± 4 ms (minimum 1027.6 ± 168.9 ms; maximum 1097.0 ± 59.5 ms) and the rMSSD index presented a mean value of 44 ± 14 ms (minimum 42.2 ± 19.8 ms; maximum 93.2 ± 65.8 ms). SDNN data were extracted, however, no meta-analysis was performed. Conclusion: Resting HR were high for the athletes' fitness level, maximal HR and RR intervals were very similar to athletes from other sports. Mean HR data do not seem to represent the real physical demand in matches and training. HRV time domain index showed low values and could be related to training loads or fatigue situations.